2021
DOI: 10.1016/j.applanim.2021.105255
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 pandemic on animal behaviour and welfare researchers

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 56 publications
6
32
0
Order By: Relevance
“…A pause in the tenure and promotion clock was suggested as an effective mitigating policy by over 80% of assistant professors, including men; however, the authors point out that such policies could inadvertently increase inequalities by affecting tenure rates of women more than that of men. Similar results were evident in the study of the experiences of animal behaviour and welfare ECRs around the world (Camerlink et al, 2021). Authors reported that doctoral students and ECRs (those up to seven years after obtaining their PhD degree) had lower self-perceived productivity than senior researchers, which was associated with higher self-perceived stress.…”
Section: Key Findingssupporting
confidence: 69%
See 2 more Smart Citations
“…A pause in the tenure and promotion clock was suggested as an effective mitigating policy by over 80% of assistant professors, including men; however, the authors point out that such policies could inadvertently increase inequalities by affecting tenure rates of women more than that of men. Similar results were evident in the study of the experiences of animal behaviour and welfare ECRs around the world (Camerlink et al, 2021). Authors reported that doctoral students and ECRs (those up to seven years after obtaining their PhD degree) had lower self-perceived productivity than senior researchers, which was associated with higher self-perceived stress.…”
Section: Key Findingssupporting
confidence: 69%
“…Across all articles reviewed, online questionnaires were the most commonly applied method of data collection. Online questionnaires were used (a) as a single datacollection method in eight studies (Adarmouch et al, 2020;Aubry et al, 2021;Camerlink et al, 2021;Guintivano et al, 2021;Kappel et al, 2021;Myers et al, 2020;Ramvilas et al, 2021;Stamp et al, 2021) and (b) in conjunction with other data sources in two studies that included email exchanges, mentor's notes, and papers co-authored by the mentor and doctoral researchers, as well as their perceptions of the effectiveness of the mentoring programme or website analytics and post-conference surveys (Raby and Madden, 2021). One of the papers involved data collection in the form of documents posted to an openaccess preprint repository for social sciences (Cui et al, 2022).…”
Section: Methods and Participants In The Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concern with researchers is scarce ( 40 42 ) and it is urgent to cover this gap. Some studies, just prior to COVID-19, have been reported that researchers present high levels of stress ( 40 , 43 , 44 ). This shows that this problem existed even before COVID-19 and needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Two companion papers focused on human behaviour and well-being rather than animal behaviour. Kappel et al (2021) and Camerlink et al (2021) both conducted a survey among researchers to assess the impact of the pandemic on researchers and their research, with a focus on animal behaviour and welfare researchers. They both concluded that some groups faced more difficulties in their research work than others due to the pandemic, and these are especially early career researchers (notably PhD students) and caretakers of children.…”
mentioning
confidence: 99%